Mitigasi Abrasi Berbasis Kearifan Lokal Di Kabupaten Waropen Kampung Sanoi Dan Pantai Ronggaiwa - Reigel Albert Wonatorei; Elisabeth V. Wambrauw; Lasarus Ramandey (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Sanoi Village and Ronggaiwa Beach are villages that are located in Waropen District and are part of the province of Papua. Along the Sanoi Village Road and Ronggaiwa Beach is a road that runs along the coastline and is an accessibility route between villages and the logistics of maritime transportation which is an economic route of the Waropen District Government so abrasion handling must be carried out immediately. The study examines the extensive calculations and advance backward coastline and also the exploitation of the local wisdom of the community as an abrasion countermeasures.The research methods used to the objectives of the study are quantitative descriptive methods, spatial analysis, time series analysis and analysis of local intelligence indicators. Quantitative deskriptive analysis is by displaying field images and presenting width changes in coastlines and coastline backward velocities throughout 2012, until 2022. Spatial analyses using ArcGIS software and field observations. Time series analysis to observe the changes in the width and backward speed of coasts by looking at the 2012 image, up to 2022. Local intelligence indikator analysis is an analysis that identifies the local abilities that communities use in performing abrasion backwardness. The results of the research showed that there was a wide change of coastline and the rate of reversal of the coastal line along the year 2012 to 2022, in which four years once counted the area of blood abrasion and the speed of retrocession of coastal lines. Based on the results of observations found that the change in coastalline occurred due to the magnitude of abrasions that occurred in Sanoi Village and Ronggaiwa Beach. However, with the knowledge of local wisdom that the community possesses, it can prevent and control abrasion by using the environment to form the traditional talud that is often referred to as the local community with the name Talud Rufia.